2007
DOI: 10.1007/s00204-007-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mitogen activated protein kinase (MAPK) during carbon tetrachloride intoxication in the rat liver

Abstract: Carbon tetrachloride (CCl(4): 4 ml/kg body weight as a 1:1 mixture of CCl(4) and mineral oil) was orally administered to rats. After 12 h the activity of plasma AST (aspartate aminotransferase) and ALT (alanine aminotransferase) was significantly higher than that of the control group and plasma AST and ALT activities increased thereafter. These results indicated that the necrotic process was active at about 12 h and developed thereafter. After 2-24 h of CCl(4) administration, the hepatic level of vitamin C, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…ERK is particularly sensitive to oxidative stress and is activated by 100 mM hydrogen peroxide, i.e., as low a level as 100 mM of reactive oxygen species, in cultured rat hepatocytes, 36) so it may be difficult to detect a change of 100 mM in 2,000 mM of vitamin C in the liver, even if all hydrogen peroxide caused an equivalent decrease in vitamin C. The activation of ERK has preceded the decrease in liver ascorbate level with the oxidative stress caused by carbon tetrachloride and thioacetamide. 8,9) The vitamin C level in the present study was significantly decreased in the non-ischemic region, so the notion of ERK activation in this region is reasonable. This may be a cytoprotective reaction of the nonischemic lobes to the oxidative stress caused by I/R.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…ERK is particularly sensitive to oxidative stress and is activated by 100 mM hydrogen peroxide, i.e., as low a level as 100 mM of reactive oxygen species, in cultured rat hepatocytes, 36) so it may be difficult to detect a change of 100 mM in 2,000 mM of vitamin C in the liver, even if all hydrogen peroxide caused an equivalent decrease in vitamin C. The activation of ERK has preceded the decrease in liver ascorbate level with the oxidative stress caused by carbon tetrachloride and thioacetamide. 8,9) The vitamin C level in the present study was significantly decreased in the non-ischemic region, so the notion of ERK activation in this region is reasonable. This may be a cytoprotective reaction of the nonischemic lobes to the oxidative stress caused by I/R.…”
Section: Discussionsupporting
confidence: 55%
“…[23][24][25] The activation of MAPK is linked with cell death in the rat liver via oxidative stress. [7][8][9] The three major subclasses of the MAPK family are JNK, ERK1/2, and p38 MAPK. Phosphorylated JNK in the ischemic lobes was significantly higher 1.5 and 3 h after reperfusion when the oxidative stress was also significantly higher, as was evident by the liver vitamin C level (Table 1), and liver necrosis was active based on the plasma AST and ALT levels ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Many studies have demonstrated that lipid peroxidation of liver cell endoplasmic reticulum initiated by the trichloromethyl radical generated by the reaction between CCl 4 and cytochrome P450 is the initial event that occurs as early as 2 h after CCl 4 intoxication in rats. 1,2) Thereafter, the resulting severe oxidative stress persisted for at least 36 h 3) despite the concentration of CCl 4 in the liver having decreased rapidly from the maximal level attained at 1.5 h. 4) CCl 4 causes many intracellular events including activation of mitogen activated protein kinase (MAPK), 5,6) sphingomyelinase, 3) nuclear factor-κB (NF-κB), 7) and cyclooxygenase-2 (COX-2). 8) Humoral factors may be involved in these inflammatory events and, therefore, CCl 4 -induced hepatic injury is assumed to involve two phases.…”
mentioning
confidence: 99%